Some mechanical and chemical properties of cement stabilized Malaysian soft clay - Ho, Meei Hoan (2008)
Soft clays are defined as cohesive soil whose water content is higher than its liquid limits. Materials such as these display extremely low yield stresses, high compressibility, low strength, low permeability and consequently low quality for construction. Thus, soil-cement mixing is adopted to improve the ground conditions by enhancing the strength and deformation characteristics of the soft clays. For the above mentioned reasons, a series oflaboratory tests were carried out to study some fundamental mechanical and chemical properties of cement stabilized soft clay. The test specimens were prepared by varying the portion of ordinary Portland cement to the soft clay sample retrieved from the test site of RECESS (Research Centre for Soft Soil) at UTHM. Comparisons were made for both mechanical and chemical properties by relating the effects of cement stabilized clay of homogeneous and columnar system specimens for 0,5 and 10 % cement and curing for 3, 28 and 56 days. The mechanical properties examined included one-dimensional compressibility and undrained shear strength, while the chemical properties included pH values and the percentage of oxide concentration. For the mechanical properties, both homogeneous and columnar system specimens were prepared to examine the effect of different cement contents and curing periods on the stabilized soil. The onedimensional compressibility test was conducted using an oedometer, while a direct shear box was used for measuring the undrained shear strength. Chemical properties of the stabilized material were examined using the X-Ray Fluorescence (XRF) method to obtain the percentage of oxide concentration while a pH meter was used to determine the pH values. The chemical study was also to ascertain the extent of leaching effect from the stabilized column to the surrounding soils. The higher the value of cement content, the greater is the enhancement of the yield stress and the decrease of compression index. The value of cement content in a specimen is a more vi active parameter than the curing period. It can be proposed the following relationship for RECESS soft clay from this study: cry' = 1.5871 <. The chemical results showed that cement-stabilized column give environmental effects to the soil surrounding the column. The pH values for cement content of 5 % and 10 % in the soil-cement column specimens gradually decreases with the curing days for both consolidated and without consolidated specimens. Soil-cement column specimen with consolidation gave a higher pH compare to the specimens without consolidation. Major to minor relative values ofthe percentage of oxide concentrations are Si02 > Ah03> Fe203 > S03 > K20 > CaO.